Satlogi SANTRI Pesantren Zainul Hasan Genggong Pajarakan Probolinggo: Local Genius Penguat Karakter Bangsa - Imam Bukhori (HUMANISTIKA : Jurnal Keislaman, 2020)
Culture and national character education which refer to educational of morals, values and nation character has been established since 2010. However, it movalsound is not forceful enough.By that, in 2017 government re-excavate and re-inforced the character education through nationalprogram of Reinforcement of Character Education.Educational institution becomestrategic medium because of it structures, systems and tools which has dispersed in Indonesia entirely from the outlying district to the navel. The national character education is expected carried out massively and systematically by the program that is integrated in the entire educational system, school culture, and in collaboration with community. The main values of character implemented are religius, nationalist, be autonomous, mutual assistance, and integrity. Satlogi SANTRI (the acronim of Sopan Santun, Ajeg/Istiqamah, Nasehat, Taqwallah, Ridlallah, and Ikhlas Lilahi Ta’ala) six values that has been established by KH. Moh. Hasan Saifourridzall as a local genius of PesantrenZainulHasanGenggong since 1989, are basic precept, purpose and direction of behavioral rules should be hold by santri in PesantrenZainulHasanGenggong. And the six values become focus of learning, customary and cultural practice. SatlogiSANTRI as the values which contain islamism, nationalism concepts grounded on humanism values staunch to moral principles, spiritual quotient, interpersonal dan emotional quotient in mutual accord and reinfocerd to the religius, nationalist, be autonomous, mutual assistance, and integrity values.